2008
DOI: 10.1016/j.eurpsy.2008.01.791
|View full text |Cite
|
Sign up to set email alerts
|

The VADO approach in psychiatric rehabilitation: A randomized controlled trial

Abstract: Objective:This study investigated whether a specific planning and evaluation approach called VADO (Skills Assessment and Definition of Goals) resulted in improved personal and social functioning among patients with chronic schizophrenia.Methods:A total of 85 patients with chronic schizophrenia were randomly allocated to the VADO-based intervention or to routine care; 78 completed the program. Interventions were carried out in nine Italian day treatment or residential rehabilitation facilities. Assessment at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
1
13
0
2
Order By: Relevance
“…However, the lack of effect on the other secondary outcomes contrasts with earlier findings that reported changes in the areas of housing and quality of life, 19 and improvement in general functioning. 20 A possible explanation is that these studies focused on groups with more severe problems, such as homelessness, whereas in the current study goals were directed at more subtle changes, which may have led to a ceiling effect. It is also possible that for these more subtle changes, goal attainment constitutes a more sensitive outcome than generic measures assessing functioning or quality of life, 44,45 measuring, for instance, subtle improvements in residential conditions other than independent living.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the lack of effect on the other secondary outcomes contrasts with earlier findings that reported changes in the areas of housing and quality of life, 19 and improvement in general functioning. 20 A possible explanation is that these studies focused on groups with more severe problems, such as homelessness, whereas in the current study goals were directed at more subtle changes, which may have led to a ceiling effect. It is also possible that for these more subtle changes, goal attainment constitutes a more sensitive outcome than generic measures assessing functioning or quality of life, 44,45 measuring, for instance, subtle improvements in residential conditions other than independent living.…”
Section: Discussionmentioning
confidence: 92%
“…Shern et al 19 reported that homeless psychiatric patients receiving PR improved on unmet needs, housing status, quality of life, and psychological health. Gigantesco et al 20 observed an improvement in social functioning in patients engaged in a rehabilitation program inspired by PR, compared with the control subjects. However, in an RCT on vocational rehabilitation reported by Rogers et al, 21 PR and control groups displayed similar improvement in work participation.…”
mentioning
confidence: 98%
“…A escala PsP pode ser usada como um instrumento confiável e de fácil aplicação na mensuração dos resultados obtidos (Gigantesco et al, 2006).…”
Section: Discussionunclassified
“…Table I summarizes the learning from critically appraising the literature and reviewing the best practices in rehabilitation. The most robust evidence is at the base of the table because these principles are well supported by the empirical evidence (for example, Hamera and Brown, 2000;Gigantesco et al, 2006;Burns et al, 2007). The title for each box, written in italics, is a key principle of living skills training.…”
Section: Building Blocks For the Living Skills Training Programmentioning
confidence: 98%
“…Skills training in relation to task (Appelo, 1992;Brown et al, 2002;Swildens et al, 2003;Woonings, 2003;Gigantesco et al, 2006;Eklund, 2007;van Weeghel, 2010; Landelijke Stuurgroep Multidisciplinaire Richtlijnontwikkeling in de GGZ, 2012)…”
Section: Shared Decision Makingunclassified